2012
DOI: 10.3136/fstr.18.515
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Roasting by Superheated Steam and by Convection on Changes in Colour, Texture and Microstructure of Peanut (Arachis hypogaea)

Abstract: Keywords: superheated steam, convection, roasting, physical characteristics, peanut, Arachis hypogaea *To whom correspondence should be addressed. E-mail: taris@usm.my IntroductionCooking represents an important step in food preparation as its acceptability by the consumer is dependent on the heat-induced reactions affecting the colour, aroma, flavour and texture quality of the final product. The correct choice of temperature, time and humidity could trigger the desired chemical reactions (protein denaturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In a typical set‐up, saturated steam from a steam generator is heated up in a heater and becomes superheated steam, which is then introduced into a drying chamber wherein a product to be dried is placed. In the case of roasting, superheated steam has been applied to many products, including coffee beans (Maki and Haruyama ), peanuts (Idrus and Yang ), and cocoa beans (Zzaman and Yang ; Zzaman and others , ). Quality improvement of the products has been reported in terms of flavor, taste, color, texture, and retention of antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In a typical set‐up, saturated steam from a steam generator is heated up in a heater and becomes superheated steam, which is then introduced into a drying chamber wherein a product to be dried is placed. In the case of roasting, superheated steam has been applied to many products, including coffee beans (Maki and Haruyama ), peanuts (Idrus and Yang ), and cocoa beans (Zzaman and Yang ; Zzaman and others , ). Quality improvement of the products has been reported in terms of flavor, taste, color, texture, and retention of antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…(Varela et al 2006). It is worth mentioning that fracturability is a defining textural characteristic of extruded and crunchy products such as puffed snacks and cereals (Idrus and Yang 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A Recent study has shown that superheated steam can reduce lipid oxidation, retain vitamin C, and preserve color and texture of various foods (Idrus and Yang, 2012;Zzaman and Yang, 2013;Abdulhameed et al, 2014). These criteria make it an attractive alternative to cooking fish with minimal amino acid and PUFA destruction.…”
Section: Introductionmentioning
confidence: 99%